APPLICATION OF MOBILE TECHNOLOGIES IN ADVANCED TRAINING - Sherzod Xujakulov (FAN, TA'LIM VA AMALIYOT INTEGRATSIYASI, 2021)
This article discusses the content, advantages and peculiarities of teaching on the basis of mobile technologies, one of the promising areas of education.